Increasing Students' Empathy and Counseling Self-Efficacy Through a Mindfulness Experiential Small Group. Issue 4 (1st October 2016) - Bohecker, Lynn; Doughty Horn, Elizabeth A.
Abstract : This study used the Solomon 4-group design to examine the relationship between a mindfulness experiential small group (MESG) and mindfulness skills, empathy, counseling self-efficacy, and perceived stress for counselors in training (CITs). Understanding how the MESG affects these characteristics provides essential information to inform the development of targeted interventions and programs in counselor education. Twenty-two 1st-semester 1st-year CITs participated and were randomly assigned to one of 4 groups. The findings suggest the MESG may influence the capacity for students to stay present and empathize with a client with higher counseling self-efficacy.